(untitled) (Academia Journal of Medicine, 2021)
Background: To study the alterations in thyroid hormone levels in critically ill patients. Subjects and Methods: Fasting venous blood samples were collected on admission to ICU from all critically ill patients and were subjected for thyroid hormone analysis by VIDAS-ELISA. They were also be evaluated for body temperature, blood pressure, pulse rate, respiratory rate, and impairment of consciousness on the Glasgow coma scale. Arterial blood gas analysis, complete blood count, liver function test, renal function test was interpreted, and the APACHE II score was calculated. Course and the outcome of these patients were followed in the hospital. Result: Maximum patient belong to 41-50 years age group (n=34, 34%) Maximum patients were male (n=69, 69%) and rest were females (n=31, 31%). 42 (42%) patients required Ventilator assistance. The mean APACHE-II score was significantly higher among non-survivors compared with survivors (25.52 ± 6.84 vs. 14.06 ± 5.71, P < 0.01). The mean value of TSH was 3.27±6.91. The mean value of FT3 was 3.42±0.36. The mean value of FT4 was 14.79±1.17. A total of 22 patients (22%) succumbed to their illness during ICU admission. The mean level of both FT3 and FT4 were lower in non-survivors (2.98, 13.39) as compared to survivors (3.82,15.71). The mean level of TSH was lower in non-survivors (2.63) as compared to survivors (4.07). Conclusion: FT3 and FT4 was lesser in non-survivors as compared to survivors with significant difference. Although TSH level was lower in non-survivors as compared to survivors, but there was not statistically significant difference.FT3 and FT4 were the best independent predictors of ICU mortality.